Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Kopi Susu Baper Di Masa Pandemi Covid-19 - Habibuhrahman Habibuhrahman; Veronica Veronica; Herry Gunawan S (Universitas Mitra Indonesia, 2022)
AbstractThe coffee industry in Indonesia is growing very quickly due to the increasing demand for coffee and can create many coffee shop business opportunities in Indonesia. The increase in coffee shops in Indonesia continues to increase, one of which is in the province of Lampung, namely the Baper Milk Coffee Shop in Metro City, Lampung. The purpose of this research is to find out the marketing strategy carried out by the owner of the Baper Milk Coffee Shop in Metro City during the Covid-19 pandemic. The measuring instrument used in this research is observation, interviews and questionnaires as well as using SWOT analysis. Based on the results of the SWOT analysis, the total calculation of IFAS is 3.60 and EFAS is 3.62. From the results of the SWOT Cartesian diagram, it is known that Kedai Kopi Susu Baper in Metro City is in quadrant I, namely aggressive growth (Growth Oriented Strategy), where this situation is quite profitable, namely growth. And 11 alternative marketing strategies have been formulated that can be used by Kedai Kopi Susu Baper. Keywords: COVID-19, Marketing Strategy, SWOT Analysis